Penerapan Metode Prototipe Dalam Pembangunan Website Promosi Dusun Gedong Menggunakan CMS Wordpress - Suharyadi, Suharyadi; Maria, Evi; Purwanto, Purwanto (Building of Informatics, Technology and Science (BITS), 2022)
Abstract–Gedong Hamlet is one of the hamlets in the Tajuk village area, Getasan District, Semarang Regency, Central Java Province. This hamlet is located on the slopes of Mount Merbabu at an altitude of 1,700 meters above sea level. Road access to this village is quite difficult and can only be passed by one four-wheeled vehicle. This hamlet has tourism potential of amazing natural beauty and abundant produce through vegetables. However, the difficulty of access to this hamlet makes the potential of the hamlet less well known by the public. This study aims to promote the potential of Gedong hamlet so that it is known and the wider community can get to know Gedong hamlet. So with the recognition of this hamlet, it is hoped that many visitors will come to enjoy the natural potential of Gedong hamlet and the potential of agricultural products, so that it can further improve the economy of the people of Gedong hamlet. The solution used to overcome this problem is to build a website that contains a profile of Gedong hamlet, natural potentials, and market tourism packages in Gedong hamlet. Website development using CMS Wordpress which is an open source application and is supported by many plugins, and this CMS has been widely used by other large websites. The result is that orders can be immediately responded to by the manager, making it easier for both managers and prospective tourists to transact